2015
DOI: 10.1063/1.4927671
|View full text |Cite
|
Sign up to set email alerts
|

Design strategies for self-assembly of discrete targets

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 71 publications
0
50
0
Order By: Relevance
“…[4][5][6][7][8] In the past few years, several theoretical and computational studies have also been undertaken, probing the intriguing self-assembly behaviour exhibited by such systems. [9][10][11][12][13][14][15][16][17][18] We have previously shown that the DNA brick self-assembly is made possible by the interplay between self-assembly and growth. In particular, as a system of DNA bricks is cooled, at some tempera Department of Chemistry, University of Cambridge, Lensfield Road, Cambridge, CB2 1EW, United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] In the past few years, several theoretical and computational studies have also been undertaken, probing the intriguing self-assembly behaviour exhibited by such systems. [9][10][11][12][13][14][15][16][17][18] We have previously shown that the DNA brick self-assembly is made possible by the interplay between self-assembly and growth. In particular, as a system of DNA bricks is cooled, at some tempera Department of Chemistry, University of Cambridge, Lensfield Road, Cambridge, CB2 1EW, United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…σ ang determines how quickly the potential decays with any deviation from perfect alignment and is set at 0.2 in this work. 16 The embedded interaction sites with angular attenuation are similar to a previous model for patchy spherical particles. [35][36][37] Each patch is also given an intrinsic orientation, pointing from the center of the face to which the patch belongs to the center of one of the face's edges.…”
Section: Patchy Potentialmentioning
confidence: 59%
“…42 However, such an approach is not advantageous in all cases. 16,43 Because of the uniqueness of building-blocks for fully addressable targets, they have no formal modularity, but a hierarchical path could nevertheless be used to limit the scope for fragment competition by controlling the fragments that are likely to arise. The performance of model A5 is shown in Fig.…”
Section: Heterogeneous Bond Energiesmentioning
confidence: 99%
“…It became rapidly apparent that even in such simplified systems it is necessary to have a minimum number of residue types to encode the target configurations (31). Moreover, such simple models allowed to explore the related question on how the alphabet size influences protein-protein interactions (32)(33)(34)(35). Finally, works done on realistic models, offer substantial evidence that protein design with a minimalistic alphabet is possible (36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…The results show that for the folding of a small protein the minimum number of amino acid types needed is just 4. However, such a small alphabet compromises the heterogeneity of the protein-protein interactions (21,29,(33)(34)(35) and binding cannot be avoided.…”
Section: Introductionmentioning
confidence: 99%